IN VITRO AND IN VIVO REMOVAL OF ORAL ANTIDIABETIC AGENTS (METFORMIN) USING ACTIVATED CARBONS - Valente Nabais, Joao (2012)
Diabetes is the most worldwide common chronic disease, according the International Diabetes Federation [1], more than 32 million citizens living in the European Union have diabetes, representing nearly 10% of the population, to which we should add equal number of people suffering from impaired glucose tolerance. Diabetes prevalence is growing at alarming rate worldwide, being of particular relevance the type 2 diabetes. Nowadays 285 million people worldwide live with diabetes and it is expected that this numbers will increase by 20% until 2030 due to obesity and the ageing of the population [1]. This growth leads to an increasing consumption of drugs such as oral antidiabetics. Metformin is one of the active principles most commonly used for this purpose being among the pharmaceuticals with the highest production numbers worldwide to treat type 2 diabetes because is cheap, has high level of tolerance and when used in the prescribed dosage is very secure with minimal side effects. However, in case of overdose of metformin upon a ingestion of more than 10 times the prescribed dosage, accidentally or on propose, lactic acidosis and low blood pressure can occur. Overdoses with metformin are relatively uncommon, but may have serious consequences, if medical attention is not given on time, it may lead to coma and ultimately death Because of its spread use another problem must be taken into consideration, which needs to be addressed, the occurrence of metformin residues in sewage and surface waters due to improper discharge of the non-used tablets to regular garbage [2]. This situation is becoming a serious problem of environmental pollution and public health. This paper reports the use of activated carbon produced from biomass for the removal of metformin in 2 different settings. On one hand, from aqueous solutions and, in another hand, from simulated biological fluids (gastric and intestinal) conjugated with in vivo testing.